Evaluation of small steel fiber for enhancing reinforced concrete flexural characteristics - Azimah, Hazeli (2012)
Improving construction material with minimum cost is main goal of construction industry and in this regard several researches have been documented. To improvement of plain concrete quality and reducing construction cost a new simple technique has been suggested. The small steel fiber in different length directly has been used in concrete mixed design for modifying plain concrete fractural characteristics. The main objectives are evaluating length and percentage of small steel fiber in modifying plain concrete flexural characteristics. The result indicated that this method is one of the easiest and cost effective techniques and also less time is required for enhancing plain concrete flexural characteristics. It has been find that if steel fiber length of 50 mm shown better performance compare to when steel fiber length is 10 mm, 20 mm and 40 mm. The limitation was the smooth steel fiber is used and the result could be better in application of deformed steel fiber or rough surface steel fiber.